Description Of the Escherichia Coli Content in The Drinking Water of Diarrhea Sufferers in Gebangan Village - Prasetyo, Fikri Putra; Nurika, Globila (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
Diarrhea is a digestive system disorder characterized by the frequent passage of stools three or more times a day. According to Riskesdas, the prevalence of diarrhea in Indonesia in 2018 was 8%, translating to 1 million cases. Generally, diarrhea is caused by the Escherichia coli bacteria, which can be present due to contamination from open defecation and livestock waste. This study employs a quantitative approach with a descriptive research design. The research was conducted in Gebangan Village, involving ten respondents diagnosed with diarrhea between July and December 2022. Examining the host factors, it was found that most respondents did not treat their drinking water (60%) and consumed less than 2 liters of water per day (70%). Regarding environmental factors, 70% of respondents sourced their drinking water from drilled wells or pumps, and the majority (70%) had a piping system at their drinking water source. Additionally, 50% of respondents had their drinking water source located less than 10 meters from pollutant sources. Regarding the agent factors, the physical parameters of drinking water for all respondents (100%) indicated no taste and no odor. However, 50% of respondents reported that their drinking water was colored. The assessment of Escherichia coli content in the drinking water of the ten respondents revealed that only one respondent (10%) had drinking water contaminated with Escherichia coli bacteria. Future researchers are encouraged to investigate drinking water containers and other factors that can influence the presence of Escherichia coli, such as clean and healthy living behaviors and food sanitation.